Impact of Tween 60 on physicochemical properties and stability of Pistacia lentiscus fruit oil-in-water emulsion at a semi-low temperature. Issue 3 (4th March 2019) - Chadli, Samir; Mourad, Lounis; El-Hadj, Abdellah; Aissou, Mouhamed; Boudjema, Fatiha
Abstract: This study shows the effects of the Tween 60 emulsifier at different concentrations on the aqueous emulsion containing 5% of Pistacia lentiscus fruit oil. The rheological behavior and the droplet size distribution of cosmetic oil-in-water emulsions were investigated. This investigation was carried out by analyzing the shear flow and dynamic oscillatory followed by microscopic analysis and physical stability study for 24 hours and 4 months. During the period of 4 months, the emulsions were stored in a refrigerator at a semi-low temperature 12 °C. The physical stability test showed that the sample not emulsified yielded a creaming process after a short aging time. Flow curves of emulsions prepared with TW 60 exhibited a non-linear relationship between the shear stress σ and shear rate γ ̇, which implies that the Herschel–Bulkley rheological model was the appropriate model for the shear flow. The increase of emulsifier quantities leading to an increase in the internal structure coherence, whereas the excess quantity affects the structure. Therefore, the optimal quantity proposed was 3.47%. Furthermore, the storage time at a semi-low temperature performed the stability and maintain the structure of emulsions. Graphical Abstract: